2006
DOI: 10.1121/1.2221529
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior of wild dugongs monitored by a passive acoustical method

Abstract: Little is known about feeding behavior of wild dugongs (Dugong dugon) because direct measurements of feeding events in the water were scarcely feasible. In this study, the authors achieved the first successful feeding sound monitoring in a seagrass area using a full-band underwater recording system (called automatic underwater sound monitoring system for dugong: AUSOMS-D). In total, 175 feeding sounds were identified in 205 h of recording. Feeding sounds were only detected at night, implying diurnal difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…In Thailand, dugong calls were frequently recorded between 0300 and 0500 (Ichikawa et al . 2006), and feeding sounds of dugongs were only obtained at night (Tsutsumi et al . 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In Thailand, dugong calls were frequently recorded between 0300 and 0500 (Ichikawa et al . 2006), and feeding sounds of dugongs were only obtained at night (Tsutsumi et al . 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Such vocal exchanges may also benefit dugongs, because they are often found closer to the shore during the night (Sheppard et al, 2009 and2010;Ichikawa et al, 2006;Tsutsumi et al, 2006;Marsh and Rathbun, 1990) and in turbid shallow waters (Hines, 2005;Pollock et al, 2006;Marsh et al, 2002). Given that Florida manatees exchange vocalizations frequently during separation (O'Shea and Poché, Jr., 2006) and that Amazonian manatees have vocal signatures (Sousa-Lima et al, 2002), dugongs are likely to have a similar vocalization pattern.…”
Section: B Distance Of Wild Dugongs From the Playback Sourcementioning
confidence: 95%
“…Over the past several years, passive acoustic methods have been widely applied for monitoring dolphins ͑Philpott et al, 2007͒, porpoises ͑Wang et al, 2005͒, baleen whales ͑Stafford et al, 2007͒, and even for sirenians such as manatees ͑Phillips et al, 2004͒ anddugongs ͑Ichikawa et al, 2006;Tsutsumi et al, 2006͒. Dugongs produce several types of sounds such as chirps, trills, and barks.…”
Section: ͒mentioning
confidence: 99%
“…Underwater dugongs are visible in shallow areas such as feeding grounds. Previously in Thailand, several visual surveys were conducted to estimate the total population of about 120 animals in Trang Province ͑Hines et al, 2005͒, and acoustic observations of the dugongs suggested tidal and diel effect on their acoustic activities ͑Ichikawa et Tsutsumi et al, 2006͒. Although those previous works provided important information of the dugongs, the detection performances of the visual and acoustic observation remain to be evaluated.…”
Section: Introductionmentioning
confidence: 98%